Developing STREAM Based Pancasila Student Profile Strengthening Project (P5) Module on Chemical Bond Lesson - Khumairoh, Nurul; Okmarisa, Heppy; Refelita, Fitri; Mahartika, Ira (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The implementation of Merdeka curriculum has not long been established as the national curriculum, so many schools still lack teaching materials with limited textbooks.  This research aimed at developing STREAM (Science, Technology, Religion, Engineering, Art, and Mathematics) based Pancasila student profile strengthening project module on Chemical Bond lesson, and it was conducted with validity test by media and material experts, teacher practicality test, and student response test.  Research and Development (RnD) method was used in this research with Design and Development Research (DDR).  This research was conducted at State Senior High Schools 14 and 1 Pekanbaru.  The research findings showed that the validity scores were 82.6% by media experts with very valid category and 87.45% by material experts with very valid category.  The result of teacher practicality test showed that the mean was 93.84%, and it was on very practical category.  The last test was student response test, the result was 83.58%, and it was on very valid category.  The research findings showed that STREAM-based P5 teaching module developed was very valid, practical, and interesting for students.